2016
DOI: 10.19056/ijmdsjssmes/2016/v5i2/100606
|View full text |Cite
|
Sign up to set email alerts
|

Penile Fracture:Presentation, Management and Erectile Function Following Surgical Repair

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is reported that 30.8% of patients developed voiding dysfunction, of which 50% patients were associated with urethral injury (Hatzichristodoulou et al, 2013). Another study showed that 16.6% of patients had urethral injury but did not complain about urinary symptoms during follow up (Vig et al, 2016). Another study gave evidence that 27.5% of patients had urethral injury (De Luca et al, 2017) during surgical correction of a fractured penis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 30.8% of patients developed voiding dysfunction, of which 50% patients were associated with urethral injury (Hatzichristodoulou et al, 2013). Another study showed that 16.6% of patients had urethral injury but did not complain about urinary symptoms during follow up (Vig et al, 2016). Another study gave evidence that 27.5% of patients had urethral injury (De Luca et al, 2017) during surgical correction of a fractured penis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that four-fifth participants (80%) were able to maintain their normal erectile function, and they were satisfied with their performance. A study reported that 87.5% of patients able to maintain an adequate erection (Vig, Vig, & Suchak, 2016). 91.6% patients were able to maintain adequate erectile function following surgical correction (Ateyah et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 30.8% of patients developed voiding dysfunction, of which 50% patients were associated with urethral injury (Hatzichristodoulou et al, 2013). Another study showed that 16.6% of patients had urethral injury but did not complain about urinary symptoms during follow up (Vig et al, 2016). Another study gave evidence that 27.5% of patients had urethral injury (De Luca et al, 2017) during surgical correction of a fractured penis.…”
Section: Discussionmentioning
confidence: 99%